Employee relations and communication dimensions as antecedents of organisational commitment : A case study of selected hotels in Kuching, Sarawak - Deborah Puspamani, A/P Kanagendram (Universiti Malaysia Sarawak, (UNIMAS), 2001)
This is a cross-sectional study concerning how employee relations and communication variables influence workers commitment in selected 3-star, 4-star and 5-star hotels in Kuching. The dependent variable was organizational commitment, while eleven independent variables (loyalty, job satisfaction, motivation, employee-supervisor relation, training, recognition, teamwork, communication, methods of communication, status differential and language) were studied.